The development of human primary hepatocyte model for investigating the pathogenesis of the hepatitis C virus - Dexter, Laura Joanne (2010)
The blood-borne virus, hepatitis C (HCV), is causing an increasing burden of chronic and terminal liver disease, world-wide. The development of successful drug treatments for this infection has been hampered by the lack of an efficient and physiologically relevant in vitro model of viral pathogenesis. The recent characterisation of the JFH1 clone of HCV, which is capable of both infection and replication in some types of cell lines, has revolutionised the potential of in vitro HCV research. Yet very few studies have been able to investigate the pathogenesis of HCV in normal, healthy hepatocytes, and none has examined the effects of such infection on other human liver cells. This thesis presents the techniques and results of work to optimise human primary liver cell cultures, in order to permit investigation of the JFH1 clone of HCV. A protocol was developed for the isolation of healthy human hepatocytes from surgically resected liver tissue. Methods for the non-viral transfection of primary hepatocytes were then optimised and compared. Finally, the expression of a JFH1 replicon (incorporating the luciferase marker gene) was assessed in human primary hepatocytes, both in monoculture and in three-dimensional co-culture with hepatic stellate cells (HSCs). The level of expression of the JFH1 replicon in human primary hepatocytes was considerably lower than that found in the human hepatoma Huh7 cell line, as expected, and highly dependent upon the batch of primary cells used. Hepatocytes which were grown in co-culture with HSCs showed some evidence of a greater capacity to support the translation and replication of JFH1. Luciferase was largely undetectable by 48 hours, particularly in hepatocyte-HSC co-cultures, suggesting that innate anti-viral mechanisms are preserved in these cultures. Further studies, to examine the intriguing dialogue between these models and JFH1, now have the potential to provide unique insights into the pathogenesis of HCV in the human liver.